Upaya Peningkatan Kemampuan Atlet Kancah Internasional (Studi Pada Bidang Pembinaan Dan Prestasi PTMSI Kota Prabumulih) - Sitorus, Suwanda (Jurnal Ilmiah Bina Manajemen, 2019)
The purpose of this study was to measure and evaluate how athlete's was supported by a grant from the City Government through (KONI) the Indonesian National Sports Committee to the Sports Branch (PTMSI) Indonesian Table Tennis Association Prabumulih performance of the Management of the Secretariat of Sports Organizations supported by City Government and the Council Regional People's Representative (DPRD). This study uses a descriptive, quantitative and qualitative analysis technique that is measured and analyzed from several variables and indicators. By encourage achievement, creating world class achievements. Where every sports lover and all sports and government officials are responsible for the achievement of the 2032 Olympics. However, applying it needs financial support from the government so that it is a systematic attempt to redesign the Sports Organization Secretariat in the athlete achievement training system in a way that can adjust yourself with the demands of achievement and to achieve new goals.